Yearbook of International Humanitarian Law 2013
VIII, 369 p. 1 illus.
Keywords: This volume contains several articles on ‘Detention in non-international armed conflict’, including the Copenhagen Process, and moreover features contributions on autonomous weapons systems, Apartheid and the second Turkel Report. It also contains an elaborate ‘Year in Review’ and a special section on the high-level Symposium ‘Boundaries of the Battlefield’ (The Hague, January 2013), including in-depth reflections on various other aspects of the Symposium. The Yearbook of International Humanitarian Law is the world's only annual publication devoted to the study of the laws governing armed conflict. It provides a truly international forum for high-quality, peer-reviewed academic articles focusing on this crucial branch of international law. Distinguished by contemporary relevance, the Yearbook of International Humanitarian Law bridges the gap between theory and practice and serves as a useful reference tool for scholars, practitioners, military personnel, civil servants, diplomats, human rights workers and students.